EFFECTIVENESS IMPLEMENTATION OF THE KEPUTRIAN PROGRAM FOR STUDENT’S SENIOR HIGH SCHOOL BANTEN, INDONESIA - Rohimat, Sonny; Fauzi, Anis; Hidayat, Wahyu; Alkafi, Kurnia; Heriansyah, M Arie Firdaus (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2024)
The development of school management with consideration of religious background and gender has been carried out at SMA Negeri 6 Kota Serang through various student programs. This study aims to analyze the effectiveness of implementing the female student program for Muslim female students held at SMA Negeri 6 Kota Serang. This study was conducted through an online survey of Muslim female students in grade XI of the 2024/2025 academic year, 65 female Muslim students in grade XI at SMAN 6 Kota Serang in the 2024/2025 academic year, or 73% of the population used, namely Muslim students in grades XI-A1 to XI-A4. Respondents were female students in study groups who received a female schedule the same week. This study provides an overview of the effectiveness of the female student program held at SMA Negeri 6 Kota Serang regarding the intensity of respondent attendance, activity materials, speakers or resource persons, place of activity, and the schedule. The highest level of effectiveness is shown in material selection, while the lowest is in time selection. The research results can be used to organize Keputrian programs or similar programs.